2020
DOI: 10.2967/jnumed.120.244939
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Imaging of Bacterial Infection: The State of the Art and Future Directions

Abstract: Learning Objectives: On successful completion of this activity, participants should be able to describe (1) the clinical justifications for using nuclear medicine techniques in imaging bacterial infections; (2) the mechanisms of nuclear imaging methods used to detect bacterial infections; and (3) the bacterial-metabolism specific imaging techniques currently under development. Financial Disclosure: Dr. Ohliger travels and speaks for General Electric. The authors of this article have indicated no other relevant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 71 publications
(145 reference statements)
0
54
0
Order By: Relevance
“…The development of metabolic tools that allow detections of bacteria-specific metabolism in a specific and noninvasive fashion has been an ongoing interest for many research groups. In the last decade, several agents have been developed that explicitly target bacteria-specific metabolic pathways, especially using clinically translatable nuclear imaging technologies such as PET [ 42 ]. Magnetic resonance studies targeting bacteria-specific metabolism have been infrequently reported.…”
Section: Bacteria-specific Dmimentioning
confidence: 99%
See 1 more Smart Citation
“…The development of metabolic tools that allow detections of bacteria-specific metabolism in a specific and noninvasive fashion has been an ongoing interest for many research groups. In the last decade, several agents have been developed that explicitly target bacteria-specific metabolic pathways, especially using clinically translatable nuclear imaging technologies such as PET [ 42 ]. Magnetic resonance studies targeting bacteria-specific metabolism have been infrequently reported.…”
Section: Bacteria-specific Dmimentioning
confidence: 99%
“…In addition, the high abundance (99.98%) and sensitivity (highest gyromagnetic ratio) of the hydrogen nucleus has led to rapid evolution of tools for 1 H NMR including many spectroscopic methods that are now integrated into routine clinical practice, especially for the characterization of prostate tumors [ 33 , 34 ], brain tumors [ 35 , 36 , 37 ], and various other metabolic derangements [ 38 , 39 , 40 ]. As far as other metabolic imaging tools, PET has also been extraordinarily successful especially with the rapid proliferation of metabolite-derived tracers and the expansion of dual modality scanners (i.e., PET-CT and PET-MR) [ 41 , 42 , 43 , 44 ]. Finally, imaging of other stable isotopes (i.e., 13 C) has benefitted from dynamic nuclear polarization (DNP) [ 45 , 46 ], where the nuclear polarization (and therefore the MR signal) is transiently increased by several orders of magnitude prior to injection.…”
Section: Introductionmentioning
confidence: 99%
“…There has been increasing interest recently regarding FDG PET-CT for imaging infections [ 25 ] [ 26 ], including enthusiastic publications regarding its application to FUO [ 27 ]. When the 2 techniques were compared directly or indirectly in a relatively small number of patients with FUO, FDG PET-CT outperformed WBCS [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial infection remains a serious worldwide concern being one of the significant causes of morbidity and mortality (Polvoy et al, 2020). In recent years, the issue escalated by the accelerated emergence of multidrug‐resistant pathogens due to inappropriate and/or overuse of antibiotics (El‐kawy et al, 2016; Karaiskos et al, 2019).…”
Section: Introductionmentioning
confidence: 99%